The power of forgiveness in a broken world: An understanding of forgiveness in Ephesians - Cornelius, Elma M. (HTS teologiese studies, 2021)
South Africans live in a broken country where hatred leads to violence and destroys the relationships between people. The pertinent question here is: Is forgiveness between South Africans possible? This article is an attempt to understand ‘forgiveness’ in Ephesians, and to discuss the power of such forgiveness in a violent and broken South Africa. Ephesians 4:23 demands a change in the people’s mindset in order to be able to, inter alia, be kind and compassionate when they forgive each other (Eph 4:32). This forgiveness means to take control as a believer and to use one’s power as a Christian to forgive because God forgave us. We need to be the initiators of the transaction. Forgiveness is a ‘means for imitating God’, for ‘carrying out God’s plan’, and ‘enhancing one’s relationship’ with God. Forgiveness will restore relations; it is a gift to oneself and to others, to society, to one’s country. Ephesians advises to no longer rehearse and re-think the memories of pain, to stop harbouring and nursing grudges, to stop playing the victim and perpetuating negative emotions associated with this rehearsing, and to break people’s commitment to remain angry.Contribution: Ephesians aims to persuade believers that forgiveness is a choice to imitate God. Forgiveness is an act out of grace, kindness, and compassion.